A simplified higher-order shear deformation theory for hygrothermal analysis of FRP bridge deck. (2016) - Sit, Moumita; Ray, Chaitali
A simplified numerical procedure has been developed to study the hygrothermal bending behaviour of fibre reinforced plastics bridge deck. The bridge deck has been modelled as a combination of laminated plates and closely spaced box-shaped stiffeners using the finite element method. The eight noded isoparametric plate bending element with seven degrees of freedom per node is used to formulate the plate element. The box-shaped stiffeners are modelled using three noded isoparametric beam element having same degrees of freedom per node as the plate element. A computer code has been developed in MATLAB 2013. The stress distributions throughout the thickness of the deck plate are determined considering third order shear deformation theory (TSDT) as well as first order shear deformation theory (FSDT). A comparative study of FSDT and TSDT under thermal and moisture load is presented here. The temperature distribution over the surface of the deck plate is considered here in two ways, namely, uniform temperature distribution and sinusoidal temperature distribution over the surface of the deck. The elevated moisture concentration has been considered to be uniform throughout the surface of the bridge deck.